Establishment of an Endogenous Clostridium difficile Rat Infection Model and Evaluation of the Effects of Clostridium butyricum MIYAIRI 588 Probiotic Strain - Oka, Kentaro; Osaki, Takako; Hanawa, Tomoko; Kurata, Satoshi; Sugiyama, Emi; Takahashi, Motomichi; Tanaka, Mamoru; Taguchi, Haruhiko; Kamiya, Shigeru (Frontiers in Microbiology, 2018)
Clostridium difficile is well known as an agent responsible for pseudomembranous colitis and antibiotic-associated diarrhea. The hamster model utilizing an oral route for infection of C. difficile has been considered to be the standard model for analysis of C. difficile infection (CDI) but this model exhibits differences to human CDI, most notably as most hamsters die without exhibiting diarrhea. Therefore, we attempted to develop a new non-lethal and diarrheal rat CDI model caused by endogenous C. difficile using metronidazole (MNZ) and egg white. In addition, the effects of probiotic strain Clostridium butyricum MIYAIRI 588 (CBM) on CDI were examined using this model. Syrian Golden hamsters received clindamycin phosphate orally at 30 mg/kg on 5 days before challenge with either C. difficile VPI10463 (hypertoxigenic strain) or KY34 (low toxigenic clinical isolate). Mortality and the presence of diarrhea were observed twice a day for the duration of the experiment. Wistar rats received 10% egg white dissolved in drinking water for 1 week ad libitum following intramuscular administration of 200 mg/kg MNZ twice a day for 3 days. Diarrhea score was determined for each day and fecal water content, biotin concentration, and cytotoxin titer in feces were examined. More than 70% of hamsters orally infected with C. difficile died without exhibiting diarrhea regardless of toxigenicity of strain. The rats receiving egg white after MNZ administration developed diarrhea due to overgrowth of endogenous C. difficile. This CDI model is non-lethal and diarrheal, and some rats in this model were spontaneously cured. The incidence of diarrhea was significantly decreased in C. butyricum treated rats. These results indicate that the CDI model using egg white and MNZ has potentially better similarity to human CDI, and implies that treatment with C. butyricum may reduce the risk of CDI.